2009
DOI: 10.1002/adsc.200900355
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Asymmetric Michael Reaction of Aldehydes to Nitroalkenes with Diphenylperhydroindolinol Silyl Ethers as Organocatalysts

Abstract: New dihydroindole and perhydroindole derivatives were synthesized in good yields and evaluated as chiral catalysts in the asymmetric Michael reaction of aldehydes to nitroalkenes. (2S,3aS,7aS)-Diphenylperhydroindolinol silyl ether 10 facilitated the reaction of a wide range of aldehyde and nitroalkene substrates, providing Michael adducts in nearly optically pure form (99% ee), good yields and high diastereoselectivities (syn/anti up to 99:1). These results show for the first time that perhydroindole derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…[9] Lu and Chan achieved excellent results in this reaction with a modified diphenylperhydroindol silyl ether catalyst. [10] Replacement of the phenyl groups with 1-methylimidazole in prolinol silyl ether enabled the reaction to be performed in water. [11] Palomo used 4-hydroxyprolylamides as catalysts and obtained addition products with high diastereo-and enantioselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Lu and Chan achieved excellent results in this reaction with a modified diphenylperhydroindol silyl ether catalyst. [10] Replacement of the phenyl groups with 1-methylimidazole in prolinol silyl ether enabled the reaction to be performed in water. [11] Palomo used 4-hydroxyprolylamides as catalysts and obtained addition products with high diastereo-and enantioselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Luo and Chan reported that diphenylperhydroindolinol silyl ether 34 [56], which was A novel prolinamide-camphor catalyst 35 has been discovered for the direct asymmetric Michael addition of aldehydes to nitroolefins in high yields and excellent diastereo-and enantioselectivities [57]. For the Michael addition of a, adisubstituted aldehydes to nitroolefins, the pyrrolidine-camphor catalyst 36 exhibited high efficiency under neat conditions [58].…”
Section: Asymmetric Michael Addition Reactionsmentioning
confidence: 97%
“…12 Commercially available a,a-(2-naphthyl)prolinol 4e significantly improved the ee of the product (entry 5). More sterically demanding perhydroindolinol 4f, recently employed as silyl ether derivative in enamine catalysis, 13 proved to be poorly efficient compared to prolinols 4a-e. The reaction using the most effective catalyst 4e, carried out at À16°C led to a negligible enhancement of the enantioselectivity (entry 7).…”
Section: Resultsmentioning
confidence: 99%